Individual differences in distinct components of attention are linked to anatomical variations in distinct white matter tracts - Niogi, Sumit N.; Mukherjee, Pratik; Ghajar, Jamshid; McCandliss, Bruce D. (Frontiers in Neuroanatomy, 2010)
Inter-subject variations in white matter tract properties are known to correlate with individual differences in cognitive performance in domains such as attention, yet the specificity of such linkages is unknown, both at level of specific component operations and their association with anatomically distinct networks. This study examines individual performance variation within three specific functional components of attention– alterting, orienting, and conflict processing – identified by the Attention Network Task (ANT), and relates each to inter-subject variation in a distinct set of white matter tract regions. Diffusion tensor imaging (DTI) data collected via 55 diffusion-encoding directions in a 3 Tesla MRI scan, and average fractional anisotropy (FA) was assessed within a set of individualized, a priori defined regions of interest, via the Reliable Objective Quantification Scheme (ROQS) (Niogi & McCandliss, 2006, Niogi et al., 2007). Results demonstrate three functionally distinct components of attention that each correlate specifically and distinctly with three white matter tract regions. Structure-function correlations were found between alerting and the posterior limb of the internal capsule (PLIC), orienting and the splenium of the corpus callosum, and, conflict and the anterior corona radiata (ACR). A multiple regression/dissociation analysis demonstrated a triple dissociation between these three structure-function relationships, providing evidence of three functional and anatomically separable networks. These results extend previous findings from functional imaging and lesion studies that suggest these three components of attention are sub-served by dissociable networks, and suggest that variations in white matter tract microstructure may modulate the efficacy of these cognitive processes in highly specific ways.